Most valued experiences in an international coach developer training programme - Campbell, S. M.; Fallaize, A.; Schempp, P. (International Sport Coaching Journal, 2020)
Coach developers provide education and support to coaches. Therefore, these individuals play an important role in coaching systems. However, the formal training of coach developers is a relatively new concept. Both practitioners and academics seem eager to understand how to effectively train these individuals. We had the opportunity to collect feedback from participants of an international coach developer training programme (CDTP). The primary purpose of this insights paper is to share this feedback and make recommendations for future CDTPs based on connections between participant feedback and relevant literature. A secondary purpose of this paper is to stimulate dialogue from programme participants and coordinators, who can offer additional insight regarding their experiences in CDTPs.